Influence of Zn+2 Doping on Ni-Based Nanoferrites; (Ni1−x ZnxFe2O4) - Sadaf Bashir Khan; Syed Irfan; Shern-Long Lee (Nanomaterials, 2019)
Nickel zinc nanoferrites (Ni1−xZnxFe2O4) were synthesized via a chemical co-precipitation method having stoichiometric proportion (x) altering from 0.00 to 1.00 in steps of 0.25. The synthesized nanoparticles were sintered at 800 °C for 12 h. X-ray diffraction patterns illustrate that the nanocrystalline cubic spinel ferrites have been obtained after sintering. The Scherrer formula is used to evaluate the particle size using the extreme intense peak (311). The experimental results demonstrate that the precipitated particles’ size was in the range of 20–70 nm. Scanning electron microscopy (SEM) is used to investigate the elemental configuration and morphological characterizations of all the prepared samples. FTIR spectroscopy data for respective sites were examined in the range of 300–1000 cm−1. The higher frequency band ν1 was assigned due to tetrahedral complexes, while the lower frequency band ν2 was allocated due to octahedral complexes. Our experimental results demonstrate that the lattice constant a0 increases while lattice strain decreases with increasing zinc substitution in nickel zinc nanoferrites.